Inhibition of Glycolate Oxidase With Dicer-substrate siRNA Reduces Calcium Oxalate Deposition in a Mouse Model of Primary Hyperoxaluria Type 1 - Dutta, Chaitali (Mol Ther, 2016)
Primary hyperoxaluria type 1 (PH1) is an autosomal recessive, metabolic disorder caused by mutations of alanine-glyoxylate aminotransferase (AGT), a key hepatic enzyme in the detoxification of glyoxylate arising from multiple normal metabolic pathways to glycine. Accumulation of glyoxylate, a precursor of oxalate, leads to the overproduction of oxalate in the liver, which accumulates to high levels in kidneys and urine. Crystalization of calcium oxalate (CaOx) in the kidney ultimately results in renal failure. Currently, the only treatment effective in reduction of oxalate production in patients who do not respond to high-dose vitamin B(6) therapy is a combined liver/kidney transplant. We explored an alternative approach to prevent glyoxylate production using Dicer-substrate small interfering RNAs (DsiRNAs) targeting hydroxyacid oxidase 1 (HAO1) mRNA which encodes glycolate oxidase (GO), to reduce the hepatic conversion of glycolate to glyoxylate. This approach efficiently reduces GO mRNA and protein in the livers of mice and nonhuman primates. Reduction of hepatic GO leads to normalization of urine oxalate levels and reduces CaOx deposition in a preclinical mouse model of PH1. Our results support the use of DsiRNA to reduce liver GO levels as a potential therapeutic approach to treat PH1.